THE IMPACT OF EDUCATIONAL DECENTRALISATION ON THE IMPLEMENTATION OF DEMOCRATIC PRINCIPLES IN SCHOOLS: A CASE STUDY OF THE INTERACTION BETWEEN THE CENTRAL GOVERNMENT, LOCAL GOVERNMENT, AND THE COMMUNITY - Moh. Zainudin; Aslan Aslan (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study aims to examine the impact of educational decentralisation on the implementation of democratic principles in schools, highlighting the interaction between the central government, local governments, and the community. The method used is a literature study through descriptive-critical analysis of academic literature, legislation, and previous research related to educational governance and school democratisation. The results of the study show that decentralisation provides a great opportunity to strengthen democracy in schools through increased participation of teachers, students, parents, and the community; transparency and accountability in management; and more collaborative school leadership. In this context, schools can function as laboratories of democracy that foster the values of participation, equality, tolerance, and respect for differences. However, this study also emphasises that decentralisation has the potential to create new problems, including overlapping authority between the central and regional governments, unequal capacity between regions, and community participation that is often formalistic in nature. Non-synergistic interactions between the central government, regional governments, and the community can lead to policy fragmentation and widen the gap in the practice of school democratisation. Thus, the democratisation of education in Indonesia can only be realised if decentralisation is supported by effective institutional coordination, capacity building in the regions, and the empowerment of the community as active partners in education.